“GOTCHUU!”: THE USE OF SLANG IN SOCIAL MEDIA BY GENERATION Z - Yunisrina Qismullah Yusuf; Ika Apriani Fata; Rahimatul Aini (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2022)
Slang has received much attention in research on analysis in recent years. Many studies found that slang dominated media, film, and novels. Similarly, studies on English slang received higher interest than other languages. The present study, in contrast, analyzes the slang used by Indonesian Generation Z in WhatsApp groups. The research is a qualitative study, with the researcher's primary focus in data collection being content analysis. Based on Allan and Burridge's (2006) theory, the researcher discovered 50 slang classified into seven functions: starting a relaxed conversation (27 occurrences), expressing an impression (12 occurrences), creating an intimate atmosphere (5 occurrences), addressing (3 occurrences), abusing others (3 occurrences), humiliating (0 occurrences), and expressing intimacy (0 occurrences). Furthermore, those are divided into five types: fresh and creative (7 occurrences), flippant (9 occurrences), imitative (12 occurrences), acronym (14 occurrences), and clipping (14 occurrences) (8 occurrences). In conclusion, Generation Z has used this slang to increase the intimacy of their daily WhatsApp conversations.